Terra incognita : an annotated bibliography of the Great Smoky Mountains, 1544-1934 - Bridges, Anne; Clement, Russell; Wise, Ken, 1950- (The University of Tennessee Press, 2014)
Terra Incognita is the most comprehensive bibliography of sources related to the Great Smoky Mountains ever created. Compiled and edited by three librarians, this authoritative and meticulously researched work is an indispensable reference for scholars and students studying any aspect of the region's past. Starting with the de Soto map of 1544, the earliest document that purports to describe anything about the Great Smoky Mountains, and continuing through 1934 with the establishment of the Great Smoky Mountains National Park, today the most visited national park in the United Statesh, this volume catalogs books, periodical and journal articles, selected newspaper reports, government publications, dissertations, and theses published during that period. This bibliography treats the Great Smoky Mountain Region in western North Carolina and east Tennessee systematically and extensively in its full historic and social context. Prefatory material includes a timeline of the Great Smoky Mountains and a list of suggested readings on the era covered. The book is divided into thirteen thematic chapters, each featuring an introductory essay that discusses the nature and value of the materials in that section. Following each overview is an annotated bibliography that includes full citation information and a bibliographic description of each entry. Chapters cover the history of the area; the Cherokee in the Great Smoky Mountains; the national forest movement and the formation of the national park; life in the locality; Horace Kephart, perhaps the most important chronicler to document the mountains and their inhabitants; natural resources; early travel; music; literature; early exploration and science; maps; and recreation and tourism. Sure to become a standard resource on this rich and vital region, Terra Incognita is an essential acquisition for all academic and public libraries and a boundless resource for researchers and students of the region.